Analisis Evaluasi Formatif dalam Pembelajaran IPA di Kelas 4 SDN 07 Pagi Tegal Alur - Adella Adella; Dwi Setyo Maryanti; Rizkania Fauziyah Rifai (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
Integrated learning must be based on student learning needs. Systematically in its development, it is necessary to have a formative evaluation to improve the quality of instructional programs and to be used as a reference or reference material to improve and improve the content or material of the learning outcomes. Formative evaluation in SDN 07 Pagi Tegal Alur on the subject of 36 students in elementary science learning is done by using test and non-test techniques. The test techniques used are multiple choice and description, non-test techniques using question and answer instruments, discussions, interviews, questionnaires, and observation. The results of the research on the use of formative evaluation in learning science in 4th grade elementary school proved to be effective based on the results of the pre-test and post-test.